Locomotion-dependent auditory gating to the parietal cortex guides multisensory decisions - Ilsong Choi; Seung-Hee Lee (Nature Communications)
Abstract Decision-making in mammals fundamentally relies on integrating multiple sensory inputs, with conflicting information resolved flexibly based on a dominant sensory modality. However, the neural mechanisms underlying state-dependent changes in sensory dominance remain poorly understood. Our study demonstrates that locomotion in mice shifts auditory-dominant decisions toward visual dominance during audiovisual conflicts. Using circuit-specific calcium imaging and optogenetic manipulations, we found that weakened visual representation in the posterior parietal cortex (PPC) leads to auditory-dominant decisions in stationary mice. Prolonged locomotion, however, promotes visual dominance by inhibiting auditory cortical neurons projecting to the PPC (ACPPC). This shift is mediated by secondary motor cortical neurons projecting to the auditory cortex (M2AC), which specifically inhibit ACPPC neurons without affecting auditory cortical projections to the striatum (ACSTR). Our findings reveal the neural circuit mechanisms underlying auditory gating to the association cortex depending on locomotion states, providing insights into the state-dependent changes in sensory dominance during multisensory decision-making.